THE ROLE OF INFORMATION TECHNOLOGY IN MONITORING THE HEALTH OF PREGNANT WOMEN: PERAN TEKNOLOGI INFORMASI DALAM MEMANTAU KESEHATAN IBU HAMIL - Bhakti Herwidyaningsih, Frestina; Herwidyaningtyas, Frestina Bhakti; Suhartini, Andi Mulyanti (LPPM ISTeK ICsada Bojonegoro, 2025)
Maternal health is a priority in the public health system in Indonesia, but major challenges remain, especially in remote areas with limited access to health facilities. The maternal mortality rate (MMR) is still high, caused by delays in medical treatment, lack of understanding of pregnant women about the importance of examinations, and lack of supervision during pregnancy. Information technology (IT), especially mobile applications and wearable devices, can help improve maternal health monitoring. This article aims to address these issues by utilizing technology, especially Android applications such as Diary Bunda and Pregnancy +, to support independent maternal health monitoring. The methods used include counseling and training for pregnant women in Pagerwesi Village, Trucuk District, Bojonegoro Regency. The results of the implementation of the activities showed a significant increase in pregnant women's knowledge about the role of IT in health monitoring, as well as increased awareness of the importance of using applications to monitor pregnancy conditions. This program has made a major contribution to improving the quality of maternal health and accelerating early detection of pregnancy complications. For the sustainability of this program, a more inclusive approach and increased digital literacy among pregnant women, especially in remote areas, are needed so that the benefits of information technology can be felt evenly.